Optimal Constructing Measures of Novel Research and Development Institutions in Life Sciences and Medicine in China - Hu Zhimin; Jia Xiaofeng; Yang Juntao; Qi Jianwei; Hao Sha; Xue Xiaojuan; Cheng Tao; Zhang Boli; Liu Depei (中国工程科学, 2023)
Novel research and development (R&D) institutions are an important organizational form of scientific and technological innovation in China. Novel R&D institutions in life sciences and medicine are oriented toward people’s life and health and play an important role in promoting the development of life sciences and medicine, forming multiple innovation subjects, and building an innovation ecology with active elements. However, their construction is still in an exploration stage, and it is urgent to optimize the construction strategy and form a stable and sustainable development capability. This study used the methods of policy research, on-site research, case study, and expert consultation to summarize the progress of policy promotion and exploration practices of novel R&D institutions in China, analyzed the construction modes and operation mechanisms of similar R&D institutions abroad, and presented challenges in the development of novel R&D institutions in the field of life sciences and medicine in China. On this basis, we proposed the following strategies for optimizing the construction of novel R&D institutions in life sciences and medicine in China: (1) building up a diversified and stable funding mechanism, (2) establishing a differentiated development path, (3) improving the recruiting and cultivating mechanism of outstanding professionals, (4) continuously innovating the organizational form of scientific research, (5) exploiting the advantages of the flexible mechanism for scientific achievement transformation, and (6) enhancing the academic influence of these institutions, thereby promoting the high-quality development of these institutions and the self-reliance and strength of China in science and technology.